Mathematical epidemiology in a data-rich world - Arino, Julien (Infect Dis Model, 2020)
I discuss the acquisition and use of “background” data in mathematical epidemiology models, advocating a proactive approach to the incorporation of said data. I illustrate various mechanisms for acquiring data, mainly from open data sources. I also discuss incorporating this data into models.